ANALISIS DETERMINAN STUNTING PADA BALITA USIA 24-59 BULAN DI DAERAH PERKEBUNAN (STUDI DI DESA SILO KECAMATAN SILO KABUPATEN JEMBER) - Ishomuddin, Muhammad; Ningtyias, Farida Wahyu; Ratnawati, Leersia Yusi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: In comparison to obesity and malnutrition, stunting is the most significant nutritional issue that toddlers face. Stunting has several fundamental, indirect, and indirect causes. Stunting may be brought on by the traits of plantation communities that resemble those of villages, such as low levels of education, employment, and income. It is necessary to understand the root causes of stunting in order to implement the right preventative strategies.Objective: This study's goal was to determine the reasons behind stunting in children between 24 and 59 month old in Silo Village, Silo District, and Jember Regency.Methods: Cross-sectional research was the method used in this field. The study’s population in this research was 467 families in Silo Village, a sample of 89 households and families with toddlers aged 24-59 months taken randomly using binominal proportions. Data collection on the determinants of stunting in the form of mother's education level, mother's occupation, family income, history of infectious diseases among toddlers, history of exclusive breastfeeding among toddlers, utilization of health services, and distance to health access was carried out by interview using a questionnaire. Bivariate Chi Square Test analysis of the data was done using α=0.05 significance level. If p-value<0.05, the study's findings are linked.Results: According to the findings of this study, there was no correlation between the incidence of stunting in toddlers aged 2 to 4 and the mother's education level (p=0.329), her occupation (p=0.618), the family's income (p=0.984), their history of infectious diseases in toddlers (p=0.713), their history of exclusive breastfeeding for toddlers (p=0.133), their use of health services (p=0.216), and their distance from a health facility (p=0.595).Conclusion: There is no significant relationship between the causes of stunting studied and the incidence of stunting in Silo Village, Silo District, Jember Regency. There are other causes that are thought to be more related to the incidence of stunting, namely the nutritional intake of toddlers. In future research, it is expected to examine the relationship between toddler nutritional intake and the incidence of stunting.Keywords: Determinants; Plantation Area; Stunting; Toddler ABSTRAKLatar belakang: Stunting merupakan masalah gizi terbesar yang diderita balita dibandingkan gizi buruk dan obesitas. Penyebab stunting terdiri dari penyebab dasar, penyebab langsung dan penyebab tidak langsung. Karakteristik masyarakat perkebunan yang mirip dengan masyarakat desa yaitu pendidikan rendah, jenis pekerjaan, dan pendapatan yang rendah dapat menjadi potensi penyebab kejadian stunting. Oleh karena itu penyebab stunting perlu dicari dan diketahui agar dapat dilakukan penanggulangan dan dilakukan upaya pencegahan yang tepat. Tujuan: Tujuan dari penelitian ini adalah menganalisis penyebab stunting pada balita usia 24-59 bulan di Desa Silo Kecamatan Silo Kabupaten Jember.Metode: Jenis penelitian ini menggunakan pendekatan cross sectional. Populasi dalam penelitian adalah keluarga dengan balita usia 24-59 bulan di Desa Silo berjumlah 467 keluarga dan sampel berjumlah 89 keluarga yang diambil secara acak dengan menggunakan rumus binominal. Pengumpulan data determinan stunting berupa tingkat pendidikan ibu, pekerjaan ibu, pendapatan keluarga, riwayat penyakit infeksi balita, riwayat pemberian ASI eksklusif balita, pemanfaatan layanan kesehatan, dan jarak menuju akses kesehatan dilakukan dengan wawancara menggunakan kuesioner. Analisis data dilakukan secara bivariat menggunakan Uji Chi Square dengan α=0,05. Hasil penelitian dinyatakan berhubungan apabila α <0,05.Hasil: Pada penelitian ini didapatkan hasil bahwa tidak terdapat hubungan antara penyebab stunting yaitu tingkat pendidikan ibu (α=0,329), pekerjaan ibu (α=0,618), pendapatan keluarga (α=0,984), riwayat penyakit infeksi balita (α=0,713), riwayat ASI eksklusif balita (α=0,133), pemanfaatan layanan kesehatan (α=0,216), dan jarak menuju akses kesehatan (α= 0,595) dengan kejadian stunting pada balita usia 24-59 bulan di Desa Silo Kecamatan Silo Kabupaten Jember.Simpulan: Tidak terdapat hubungan yang bermakna antara penyebab stunting yang diteliti dengan kejadian stunting di Desa Silo Kecamatan Silo Kabupaten Jember. Terdapat penyebab lain yang diduga lebih memiliki keterkaitan dengan kejadian stunting yaitu asupan gizi balita. Pada penelitian selanjutnya diharapkan meneliti hubungan antara asupan gizi balita dengan kejadian stunting.Kata Kunci: Balita; Daerah Perkebunan; Faktor Penyebab; Stunting